Pathophysiological Role of Pigment Epithelium-Derived Factor (PEDF) in Hepatic Disorders - Yamagishi, S.-I.; Matsui, T.; Kawaguchi, T.; Sata, M. (Current Medicinal Chemistry, 2010)
Pigment epithelium-derived factor (PEDF) is a glycoprotein that belongs to the superfamily of serine protease inhibitors with a potent neuronal differentiating activity. Recently, PEDF is found to be a highly effective inhibitor of pathological angiogenesis in both cell culture and animal models. Further, it has also been shown to have neuroprotective, anti-oxidative and anti-inflammatory properties, any of which could potentially be exploited as a therapeutic option for the treatment of cardiometabolic disorders, neurodegenerative disease and cancers. However, as far as we know, there are few comprehensive reviews to deal with the involvement of PEDF in hepatic disease. This article summarizes the pathophysiological role of PEDF for various liver diseases such as hepatic insulin resistance, alcoholic and nonalcoholic liver disease, and hepatocellular carcinoma, and its potential therapeutic implication in these devastating disorders.
Keywords: hepatocellular carcinoma